BANK VALUATION METHODS ANALYSIS: DEVELOMENT OPTIONS - Matvey D. Bondarenko (Статистика и экономика, 2016)
The paper considers existing businessvaluation methods. A brief description of the essence, advantages and disadvantages of each valuation method was provided. Special attention in the study waspaid to the identiﬁcation of the possibilityof using traditional valuation methods forthe purpose of bank and banking M&Adeals valuation. Based on the analysisresults further development options ofbank valuation methods were proposes.